Implementation of the Employment Termination System at MIT Al-Ishlah, Gorontalo City - Sri Ambiyah; Sitti Roskina Mas; Novianty Djafri; Arifin Suking (CV Media Inti Teknologi, 2024)
The implementation of the Termination of Employment system has rules that are per the work contract agreement mutually agreed upon by the Al-Ishlah Foundation and teachers/employees at MIT Al-Ishlah. This research aims to describe the implementation of employment relations through work agreements and the implementation of the teacher and employee termination system at MIT Al-Ishlah. The research used descriptive qualitative methods. Data was collected through interviews, observation and documentation. The results of the research show that: The implementation of employment relations through work agreements for teachers and employees at MIT Al-Ishlah, namely the appointment, placement, transfer and dismissal of teachers and employees is the full right of the Al-Ishlah Foundation after coordinating with the Madrasah Head based on a work agreement or collective work agreement with the teacher/employee concerned; In implementing the teacher and employee termination system at MIT Al-Ishlah, there are 7 types of employment termination, namely: termination of employment by the foundation, termination of employment due to sanctions imposed on employees, termination of employment due to resignation, termination of employment due to death, termination of employment due to retirement, termination of employment due to the end of the employment contract, and termination of employment work because the teacher/employee is sick for 12 consecutive months or annually. So, it is concluded that the implementation of employment relations through employment agreements for teachers and employees at MIT Al-Ishlah per Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers Article 25 paragraph 3, while the implementation of the teacher and termination system at MIT Al-Ishlah is implemented based on articles 73 and 74.